Protecting our seniors: influenza vaccination drive at UiTM Sungai Buloh - Ismail, Ilham Ameera (Faculty of Medicine, 2025)
In an effort to safeguard the health and well-being of senior citizens, the Department of Primary Care Medicine, Faculty of Medicine & Hospital Al-Sultan Abdullah (HASA), Universiti Teknologi MARA (UiTM), in collaboration with Klinik Kesihatan (KK) Rawang, successfully organised a community outreach event titled “Program Komuniti: Imunisasi Vaksin Influenza Untuk Warga Emas” on 14 July 2025. The programme was held at the lobby of the CTC, UiTM Sg Buloh Campus, from 8:00 am to 4:00 pm, targeting elderly individuals aged 60 years and above who have at least one chronic medical condition.